Non-Muslim travelers influence in choosing halal food / Mazlina Mahdzar ... [et al.] - Mahdzar, Mazlina; Zainudin, Nur Aqila Izzatie; Abd Halim, Ummi Fadzillah; Afazal, Alia Fasha (Universiti Teknologi MARA, 2021)
This study aims to examine the factors influencing non-Muslim travelers in choosing halal food in Malaysia. This study used judgmental sampling, and about 384 are randomly selected but only applicable to local non-Muslim travelers. Questionnaires were distributed to respondents at five Malay delicacy restaurants in Kuala Lumpur and were used for data analysis. The statistical analysis for social science (SPSS) was used to analyse and interpret. Regression results show a significant positive relationship between factors of food assurance, acculturation and personality traits in influencing non-Muslim travelers choosing halal food. Of these three factors, food assurance proved to have the most significant impact on halal food choice. The implications and limitations of the study are also discussed.